Urgent call to the European Commission to simplify and contextualize IVDR Article 5.5 for tailored and precision diagnostics: opinion paper - Cobbaert, Christa; Schweiger, Christian; Buchta, Christoph; Streichert, Thomas; Vanstapel, Florent; Mullier, Francois; Biaggini, Lucas; Capoluongo, Ettore; Bossuyt, Patrick; Bhattoa, Harjit Pal; Melvin, Tom; Neumaier, Michael (Clinical chemistry and laboratory medicine, 2025)
The European Commission (EC) started targeted evaluations and public consultations regarding the EU IVDR 2017/746 to assess its effectiveness, efficiency, relevance, and EU-added value. The goal is to identify implementation challenges and unintended consequences, experienced by either IVD-manufacturers that put CE-IVDs on the EU market or by medical laboratories that establish and operate in-house-IVDs (IH-IVDs) in their healthcare institution (network). Based on stakeholder feedback the EC aims to be informed about potential regulatory revisions by late 2025. As IH-IVDs, used in different modes, have a vital role in the EU healthcare system, the authors make the statement that Article 5.5 of the IVDR should be systemically amended, removing conditions (a) and (d) through (i) for in-house tests, while retaining conditions (b) and (c). Having the prime objectives of the IVDR in mind, i.e. patient safety and clinical utility, this opinion paper urges the EC to revise IVDR Article 5.5 to prevent disservices to patients and caregivers by taking into account available quality management infrastructure in ISO 15189:2022 accredited medical laboratories and guaranteed professionality of registered laboratory specialists, both already monitored at the level of the EU member states. By abandoning unnecessary, non-valuable requirements from Article 5.5 overregulation is prevented and the sustainability of important specialty and orphan tests, essential for patients with rare diseases, is guaranteed.